2014
DOI: 10.1523/jneurosci.1162-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Removal of Matrix Metalloproteinase 9 Rescues the Symptoms of Fragile X Syndrome in a Mouse Model

Abstract: Fmr1 knock-out (ko) mice display key features of fragile X syndrome (FXS), including delayed dendritic spine maturation and FXSassociated behaviors, such as poor socialization, obsessive-compulsive behavior, and hyperactivity. Here we provide conclusive evidence that matrix metalloproteinase-9 (MMP-9) is necessary to the development of FXS-associated defects in Fmr1 ko mice. Genetic disruption of Mmp-9 rescued key aspects of Fmr1 deficiency, including dendritic spine abnormalities, abnormal mGluR5-dependent LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(167 citation statements)
references
References 89 publications
7
158
0
2
Order By: Relevance
“…At the Drosophila NMJ, we recently showed that both mmp1 and mmp2 mutants strongly alter synaptic architectural development, displaying a mutual suppression mechanism between the secreted and membrane-bound enzymes . Moreover, we have shown previously that pharmacologically or genetically reducing Mmp function corrects the NMJ synaptic architecture defects in the Drosophila FXS disease model (Siller and Broadie, 2011), with similar results reported for the mouse FXS model (Sidhu et al, 2014). Therefore, we hypothesized that Mmp regulation is a major determinant of synaptic architecture.…”
Section: Timp Constrains the Pattern Of Mmp Proteolytic Activity At Nsupporting
confidence: 69%
See 2 more Smart Citations
“…At the Drosophila NMJ, we recently showed that both mmp1 and mmp2 mutants strongly alter synaptic architectural development, displaying a mutual suppression mechanism between the secreted and membrane-bound enzymes . Moreover, we have shown previously that pharmacologically or genetically reducing Mmp function corrects the NMJ synaptic architecture defects in the Drosophila FXS disease model (Siller and Broadie, 2011), with similar results reported for the mouse FXS model (Sidhu et al, 2014). Therefore, we hypothesized that Mmp regulation is a major determinant of synaptic architecture.…”
Section: Timp Constrains the Pattern Of Mmp Proteolytic Activity At Nsupporting
confidence: 69%
“…4). Motor defects have consistently been found across a range of Mmp manipulations (Brkic et al, 2015;Dansie et al, 2013;Jaworski et al, 2006;Sidhu et al, 2014), although molecular mechanisms had not been identified. Taken together, these results complete our characterization of the entire Drosophila matrix metalloproteome in controlling neuromuscular synapse structure and function .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Notably, a well-recognized feature of Fragile X syndrome in humans (ie, elongated dendritic spines that are reproduced in FMRP knockout mice) is accompanied by the excessive production of MMP-9 that, when inhibited, normalizes the spines and alleviates other pathological symptoms, both behavioral and peripheral. 15,16 The well-documented and mechanistically explained role of MMP-9 in driving synaptic plasticity coincides with the function of MMP-9 in phenomena that rely on plasticity, such as learning and memory, addiction, and epileptogenesis, which have been studied in various animal models. 5,7,[17][18][19] MMP-9 apparently plays a special role during developmental plasticity of the postnatal period.…”
Section: Mmp-9 In Physiological and Pathological Synaptic Plasticitymentioning
confidence: 84%
“…Importantly, mammalian Mmps are upregulated in neurological disorders (Huntley, 2012), including multiple sclerosis (Agrawal et al, 2008), epilepsy (Pollock et al, 2014;Wilczynski et al, 2008) and Fragile X syndrome (FXS), the most common heritable determinant of intellectual disability and autism spectrum disorders (Gatto and Broadie, 2011). Similar to the mouse FXS model (Bilousova et al, 2009;Sidhu et al, 2014), the Drosophila FXS disease model exhibits Mmp dysfunction as an underlying cause of neurodevelopmental phenotypes (Siller and Broadie, 2012). Neural defects in the Drosophila FXS model, including impairments in both morphological and functional synaptic differentiation (Doll and Broadie, 2014) are remediated by pharmacological or genetic Mmp inhibition (Siller and Broadie, 2011).…”
Section: Introductionmentioning
confidence: 99%